SPME and solvent-based GC-MS metabolite profiling of Egyptian marketed Saussurea costus (Falc.) Lipsch. concerning its anticancer activity - Engy Mohsen; Ali H El-Far; Kavitha Godugu; Fatma Elsayed; Shaker A Mousa; Inas Y Younis (Elsevier, 2022)
Background: Saussurea costus Falc with synonymous Aucklandia costus, S. lappa, and A. lappa, is an ancient perennial plant native to Himalayan region. Purpose: S. costus possesses an ethnopharmacological background for treating diarrhea, tenesmus, dyspepsia, vomiting, inflammation, and age-related diseases because it contains many chemical compounds with different biological potentials. Study design: In the current study, we investigated the phytochemical constituents of S. costus and its anticancer potential against human colon (HCT116) and hepatic (HepG2) cancer cell lines. Methods: In the current study, we identified 122 different chemical compounds using a gas chromatography-mass spectrometry (GC-MS) method and investigated its extract's in vitro anticancer activity. Results: Dehydrocostus lactone, β-caryophyllene oxide, anethole, costunolide, β-sitosterol, and γ-bisabolene were recognized by GC-MS to have an anticancer potential as stated in published studies. Vanillosmin, santolinatriene and β-Sitosterol were identified for the first time in costus oil. Therefore, in the current study, S. costus extract induced apoptotic and anti-angiogenic effects against HCT116 and HepG2 cancer cell lines using in vitro and chorioallantoic membrane (CAM) models. Furthermore, S. costus extract has successfully potentiated the anticancer effect of doxorubicin (Dox), the common chemotherapeutic agent for different cancer type treatment. Conclusion: We can consider S. costus extract as a promising agent for human colon and hepatic cancers either alone or combined with Dox.